2014
DOI: 10.1038/ejcn.2014.220
|View full text |Cite
|
Sign up to set email alerts
|

The effect of folic acid supplementation with ferrous sulfate on the linear and ponderal growth of children aged 6–24 months: a randomized controlled trial

Abstract: Folic acid had no effect on linear growth. The use of folic acid supplementation increased the monthly average weight gain and the gain in weight-for-age Z-score compared with the placebo group. This effect was independent of the dose of ferrous sulfate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Folic acid supplementation was shown in two RCTs in infants and children to have no impact on mortality ( Sazawal et al, 2006 ; Tielsch et al, 2006 ). In children over 6 months of age, two RCTs showed reduced incidence of acute diarrhoeal disease and lower respiratory tract infection ( Tielsch et al, 2006 ; Taneja et al, 2013 ) and one RCT showed increased total weight gain and WAZ scores with folic acid supplementation compared to placebo ( Medeiros et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Folic acid supplementation was shown in two RCTs in infants and children to have no impact on mortality ( Sazawal et al, 2006 ; Tielsch et al, 2006 ). In children over 6 months of age, two RCTs showed reduced incidence of acute diarrhoeal disease and lower respiratory tract infection ( Tielsch et al, 2006 ; Taneja et al, 2013 ) and one RCT showed increased total weight gain and WAZ scores with folic acid supplementation compared to placebo ( Medeiros et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Folic acid supplementation was shown in two RCTs in infants and children to have no impact on mortality 122,123 . In children over 6 months of age, two RCTs showed reduced incidence of acute diarrhoeal disease and lower respiratory tract infection 123,124 and one RCT showed increased total weight gain and WAZ scores with folic acid supplementation compared to placebo 125 .…”
Section: Efficacymentioning
confidence: 99%
“…Many micronutrients (eg, folic acid, iodine, zinc, sodium, chloride, calcium, magnesium, vitamin A, phosphorous, manganese, and pyridoxine) are important for weight and length growth in infants (11–13). Several micronutrients, including iron, zinc, copper, iodine, selenium, chloride, folate, and vitamin A, are important for brain development and brain growth, which, in turn, are related to head growth (13–15), whereas calcium, phosphorus, and vitamin D are essential for bone mineralization (16).…”
mentioning
confidence: 99%